The impact of histone deacetylase inhibition on neurobehavioural outcomes in preclinical models of traumatic and non-traumatic spinal cord injury: a systematic review - Jagodzinska, Natalia M.; Cole, Caleb; Brannigan, Jamie; Chintapalli, Renuka; Davies, Benjamin M.; Kotter, Mark R.; Mowforth, Oliver D. (Frontiers in Immunology, 2025)
IntroductionSpinal cord injury (SCI) is a traumatic injury resulting in significant life-changing disability. Elucidating the molecular processes associated with SCI may help to design novel therapeutics targeted at improving patient outcomes. Current pharmacological candidates include histone deacetylase (HDAC) inhibitors, whose anti-inflammatory properties are postulated to be of value in SCI. The objective was to synthesise the impact of HDAC inhibitors on neurobehavioural outcomes in preclinical studies of traumatic and non-traumatic SCI and to evaluate the suitability of HDAC inhibitors for clinical trials in patients with SCI.MethodsThe review was prospectively registered with PROSPERO (CRD42023477882) and conducted following PRISMA 2020 guidelines. MEDLINE and Embase were searched. Studies of animal models of traumatic or non-traumatic SCI evaluating the effect of HDAC inhibition on neurobehavioural outcomes were eligible for inclusion. Risk of bias was assessed using the SYRCLE checklist. Screening, data-extraction and risk of bias assessments were completed in duplicate.ResultsOf 10,549 studies identified, 42 studies met inclusion criteria. Animal models were rats (n=28), mice (n=13) and rabbits (n=1). SCI models included spinal cord contusion (n=24), epidural compression (n=2), vascular clip compression (n=6), hemisection (n=5), ischaemia/reperfusion injury (n=4) and dorsolateral funiculus crush (n=1). Valproate was the most frequently studied HDAC inhibitor (n=20), followed by 4-phenylbutyrate (4-PBA; n=7) and RGFP966 (n=3). Trichostatin A, tubastatin A, entinostat, PCI-34051, scriptaid, CI-994, TMP269, vorinostat, 3-TYP, SW-100 and ACY1215 were each evaluated in a single study. Three studies used the sirtuin-1 (HDAC class III) inhibitor EX527 administered with an activator molecule: melatonin (n=1), MLN4924 (n=1) and oxymatrine (n=1). Locomotor function was assessed in 98% (41/42) of studies, with improvement in locomotor outcome reported in 73% (30/41). Pain and anxiety were evaluated in one study, in which significant improvement was demonstrated.ConclusionHDAC inhibitors are associated with functional motor recovery and improved anxiety and pain scores in preclinical models of SCI. However, the results should be interpreted with caution as risk of bias of included studies was unclear. These results support further investigation of HDAC inhibitors in preclinical studies before translation into clinical trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023477882.